2016
DOI: 10.5400/jts.2015.v20i1.21-27
|View full text |Cite
|
Sign up to set email alerts
|

Ascertainment of K Nutrient Availability Class for Maize by Several Methods

Abstract: Research was conducted in Gowa, South Sulawesi at dry land farmer during two years. The aims of the research was to get the best method in ascertainment of availability class of potassium (K) for maize in dry land. The research used a single location approach, which made some of K nutrient artificial. Result of this research indicated that K nutrients class which reached by several methods are: (1) by Cate-Nelson method : two class, ie low and high class, (2) by curve continue method: two until three classes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Nilai ambang kritis yang diperoleh menunjukkan bahwa status hara tanah mempunyai nilai uji tanah yang lebih rendah dari nilai tersebut. Ambang batas kritis tersebut termasuk dalam kelas rendah, sedangkan nilai yang lebih tinggi dari nilai ambang kritis termasuk dalam kelas tinggi (Sirapa dan Tandisau, 2015). Metode grafik Cate-Nelson (Cate dan Nelson, 1971) memberikan dua kelas (kategori) pengujian tanah, yaitu kelas rendah (respon terhadap pemupukan) dan kelas tinggi (tidak ada respon terhadap pemupukan).…”
Section: Abstrakunclassified
“…Nilai ambang kritis yang diperoleh menunjukkan bahwa status hara tanah mempunyai nilai uji tanah yang lebih rendah dari nilai tersebut. Ambang batas kritis tersebut termasuk dalam kelas rendah, sedangkan nilai yang lebih tinggi dari nilai ambang kritis termasuk dalam kelas tinggi (Sirapa dan Tandisau, 2015). Metode grafik Cate-Nelson (Cate dan Nelson, 1971) memberikan dua kelas (kategori) pengujian tanah, yaitu kelas rendah (respon terhadap pemupukan) dan kelas tinggi (tidak ada respon terhadap pemupukan).…”
Section: Abstrakunclassified
“…While for K nutrient status, the the rate of K fertilizer which give the higher yield of maize for low K claas of 80 -160 kg K/ha, 40 -80 kg K/ha for moderate K class, and 20 -40 kg K/ha for high K class in Alfisols soil in Gowa District (Figure 3). Sirappa and Tandisau (2015) was reported too that K fertilization for Lamuru variety on low class nutrient is 80 kg K/ha is sufficient. -Low-P -Moderate-P -High-P Remarks: a) low : < 65 mg P/100g; moderate : 65 -90 mg P/100 g; high : > 90 mg P/100 g b) low : < 0.6 ppm; moderate : 0.6 -1.2 ppm; high : > 1.2 ppm c) low : < 0.4 mg K/100 g; moderate: 0.4 -0.6 mg K/100 g; high : > 0.6 mg K/100 g d) low : < 215 ppm; moderate : 215 -250 ppm; high : > 250 ppm ISSN 2166-0379 2018 Sirappa and Nurdin (2010), Sirappa et al (2012) reported that N, P and K fertilization with rate 300 kg urea, 200 kg SP-36 and 50 kg KCl/ha combined with 2 ton manure was give the hihgest yield of maize about 4,5 -8.6 t/ha.…”
Section: Response Of Maize To N P and K Fertilizationmentioning
confidence: 99%
“…According to Sirappa and Tandisau (2015), critical threshold values obtained with the K nutrient by Cate-Nelson graphical method are 0.3 me/100 g, 0.35 me/100 g, 178 ppm, and 213 ppm, respectively for extrantants NH 4 OAc pH 4.8, NH 4 OAc pH 7, Bray-1 and Olsen. Trehan et al (2001) reported that the knowledge of nutrient deficiency symptoms is a prerequisite for balanced plant nutrition.…”
Section: Introductionmentioning
confidence: 99%